Nanotube-based source of charges for experiments with solid helium at low temperatures: 10th International Conference on Cryocrystals and Quantum Crystals (Final part) - Borisenko, D.N.; Walmsley, P.M.; Golov, A.I.; Kolesnikov, N.N.; Kotov, Yu.V.; Levchenko, A.A.; Mezhov-Deglin, L.P.; Fear, M.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Methods of preparation of the field-emission sources of charges from carbon nanotubes suitable for study of injected charges in solid helium at low temperatures T < 1 K are presented. The sources have been prepared by arc discharge deposition of nanotubes onto a flat copper substrate or by mechanical rubbing of nanotubes into porous metal surface. The test study of the voltage-current characteristics of a diode cell with the nanotube source in super-fluid He II have shown that at voltages above 120 V one can observe a relatively large current I ≥ 10–13 A of negative charges in liquid helium. The field and temperature dependences of positive and negative currents in solid 4He were studied in samples grown by the blocked capillary technique. Usage of the nanotube based source of injected charges had permitted us for the first time to observe motion of the positive charges in solid helium at temperatures below 0.1 К. The current-voltage dependence could be described by a power law I ~ Uα, with the value of the exponent α >> 2, much higher than what one would expect for the regime of space charge limited currents.